(untitled) (Journal of Hama University, 2024)
The aim of the research is to identify the role of first-grade female teachers in developing students’ language communication skills, and to identify the differences between the average scores of teachers on a questionnaire of language communication skills that are attributed to each of the variable years of experience and academic qualification. (40) item The research was applied in the first semester of the academic year 2022/2023 on a simple random sample consisting of (187) male and female teachers from first-grade teachers from first-cycle schools in the city of Hama. The research reached the following results: - The role of first-grade female teachers in developing students’ language communication skills came with a high score on each of the sub-skills (listening - speaking - reading - writing). - There are statistically significant differences about the role of first-grade female teachers in developing language communication skills among students due to the variable number of years of experience due to the number of years from (5-10) years. - There are statistically significant differences about the role of first-grade female teachers in developing students’ linguistic communication skills due to the educational qualification variable (university). In the light of the results, the research presented a set of proposals, including holding training courses for teachers before and during service, in order to train them on methods of developing language skills for primary school students in general, and the first grade in particular.